PREVALENCE OF EARLY CHILDHOOD CARIES IN CHILDREN AGED 3–6 YEARS IN CIMAHI - Rhabiah El Fithriyah; Sri Sarwendah; Dinda Marsha Nuzwinda (Journal of Health and Dental Sciences, 2026)
Early Childhood Caries (ECC) is the occurrence of one or more tooth decay, whether the tooth has cavitary lesions or not, tooth loss due to caries, or tooth surface fillings in primary teeth of children under 6 years old. Severe Early Childhood Caries (S-ECC) is the severe form of Early Childhood Caries (ECC). S-ECC can be determined by assessing one or more smooth surfaces of primary cavities, teeth lost due to caries, and fillings that can be determined by dmfs score. The purpose of this research is to discover the incident’s description. Severe Early Childhood Caries in children aged 3-6 years in Cimahi City. The design of this study used a descriptive method with a cluster random sampling technique with children aged 3-6 years as research subjects. Early Childhood Caries can be determined by dmfs score, and Severe Early Childhood Caries can be assessed with dmfs score of more than 4 in children aged 3-4 years, a dmfs score of more than 5 in children aged 4-5 years, and a dmfs score of more than 6 in children aged 5-6 years. The results of this study were that Severe Early Childhood Caries is the most common type of ECC experienced by children aged 3-6 years, with a percentage of 57.8% and most commonly occurs in children aged 5 years, with a percentage of 54%. This study concludes that the prevalence of SECC in children aged 3-6 years in Cimahi City is the highest prevalence compared to the prevalence of non-ECC and ECC events, which is 57.8%. DOI : 10.54052/jhds.v5n3.p289-300